2020
DOI: 10.18410/jebmh/2020/646
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Masseter Muscle Thickness in OSMF Patients - A Computed Tomography Study

Abstract: BACKGROUND Oral submucous fibrosis (OSMF) is the most common precancerous lesion, prevalent mostly in South East Asia. The habit of betel nut or gutkha chewing is the main cause for this. There is a direct association between gutkha chewing habit and development of OSMF, the reason being exaggerated forces on the masseter muscle due to vigorous chewing for prolonged period of time. So, the present study was done to evaluate the thickness of masseter muscle in OSMF patients. METHODS A total of 25 subjects wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The researchers discovered that the thickness of the right side masseter muscle was greater than the left side in all but one subject, and that the difference was statistically significant. They concluded that there exists an association of masseter muscle hypertrophy with OSMF, and CT scan measurements of masseter muscle thickness were found to be statistically significant [25].…”
Section: Computed Tomography (Ct Scan)mentioning
confidence: 98%
“…The researchers discovered that the thickness of the right side masseter muscle was greater than the left side in all but one subject, and that the difference was statistically significant. They concluded that there exists an association of masseter muscle hypertrophy with OSMF, and CT scan measurements of masseter muscle thickness were found to be statistically significant [25].…”
Section: Computed Tomography (Ct Scan)mentioning
confidence: 98%